Strong Piezoelectricity in 3R‐MoS2 Flakes. (16th February 2022) - Hallil, Hamida; Cai, Weifan; Zhang, Kang; Yu, Peng; Liu, Sheng; Xu, Ran; Zhu, Chao; Xiong, Qihua; Liu, Zheng; Zhang, Qing
Abstract: Distinct from conventional 2H‐MoS2, recently synthesized 3R‐MoS2 exhibits a noncentrosymmetric atomic structure of the trigonal "building blocks" and, thus, remarkable piezoelectric characteristics of ultrathin 3R‐MoS2 flakes are predicated theoretically. This paper reveals, for the first time, very high piezoelectricity in 3R‐MoS2 flakes experimentally. Through applying mechanical stress to a 48 nm 3R‐MoS2 flake, a high output power density of 65 mW m ‐2 is obtained and is at least one order larger than those from the corresponding monolayer MoS2 flake. With out‐of‐plane lateral piezoresponse force microscopy technique, the two piezoelectric coefficients d 33 and d 13 are analyzed to be ≈0.9 and ≈1.6 pm V ‐1, respectively. These piezoelectric coefficients are not apparently dependent on the flake thickness. The findings suggest that 3R‐MoS2 is of excellent piezoelectric properties and it can be an excellent material for novel piezoelectric devices. Abstract : The strong piezoelectricity of 3R‐MoS2 flakes is clearly observed for the first time experimentally. Through applying mechanical stress to a 48 nm 3R‐MoS2 flake, a high output power density of 65 mW m ‐2 is obtained. With out‐of‐plane lateral piezoresponse force microscopy technique, the two piezoelectric coefficients d 33 and d 13 are analyzed to be ≈0.9 pm V ‐1 and ≈1.6 pm V ‐1, respectively.